Disease management in two sympatric Apterostigma fungus‐growing ants for controlling the parasitic fungus Escovopsis. Issue 11 (2nd May 2021) - Christopher, Yuliana; Wcislo, William T.; Martínez‐Luis, Sergio; Hughes, William O.H.; Gerardo, Nicole M.; Fernández‐Marín, Hermógenes
Abstract: Antagonistic interactions between host and parasites are often embedded in networks of interacting species, in which hosts may be attacked by competing parasites species, and parasites may infect more than one host species. To better understand the evolution of host defenses and parasite counterdefenses in the context of a multihost, multiparasite system, we studied two sympatric species, of congeneric fungus‐growing ants (Attini) species and their symbiotic fungal cultivars, which are attacked by multiple morphotypes of parasitic fungi in the genus, Escovopsis . To assess whether closely related ant species and their cultured fungi are evolving defenses against the same or different parasitic strains, we characterized Escovopsis that were isolated from colonies of sympatric Apterostigma dentigerum and A . pilosum . We assessed in vitro and in vivo interactions of these parasites with their hosts. While the ant cultivars are parasitized by similar Escovopsis spp., the frequency of infection by these pathogens differs between the two ant species. The ability of the host fungi to suppress Escovopsis growth, as well as ant defensive responses toward the parasites, differs depending on the parasite strain and on the host ant species. Abstract : We studied two sympatric Apterostigma fungus‐growing ants (Attini) species and their symbiotic fungal cultivars which are attacked by multiple morphotypes of parasitic fungi in the genus, Escovopsis. We assessed in vitro and in vivo interactions of these parasites with their hosts to understand, in the context of a multihost, multiparasite system, the evolution of host defenses and parasite counterdefenses. While the ant cultivars are parasitized by similar Escovopsis spp., the frequency of infection by these pathogens differs between the two ant species. The ability of the host fungi to suppress Escovopsis growth, as well as ant defensive responses toward the parasites, differs depending on the parasite strain and on the host ant species.